ANALISIS PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Hayuningtyas Pramesti Dewi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study examines the effect of firm size and profitability on the timely submission of financial statements. The objects of this study are trading, service and investment manufacturing companies listed on the Indonesia Stock Exchange for the period 2019 - 2021. The research used logistic regression to test the data as many as 375 data samples. The result of testing the data is that company size and profitability both partially and simultaneously affect the timeliness of submission of financial reports in trading, service and investment manufacturing companies.